HUBUNGAN TINGKAT KECEMASAN PASIEN SECTIO CAESAREA ELEKTIF DENGAN DERAJAT NYERI POST OPERATIF DI RUMAH SAKIT SUNGAI DAREH KABUPATEN DHARMASRAYA - Anita Darmayanti; Berri Rahmadhoni; Alimurdanis, Alimurdanis; Boy Hutaperi; Taufik Hidayat (Nusantara Hasana Journal, 2023)
Post-surgery (postoperative) patients feel severe pain and 75% of patients have unpleasant experiences due to inadequate pain management. When patients complain of pain, the only thing they want is to reduce pain. Postoperative pain is influenced by several factors, one of which is anxiety. Anxiety often increases pain perception. If anxiety does not get attention, it will cause a serious pain management problem. The scope of this study was psychiatry, anesthesia, and obstetrics and gynecology. The research was conducted in April - Mei 2023. The type of research is observational analytic. The affordable population in the study were patients who underwent sectio caesarea at Sungai Dareh Hospital, Dharmasraya Regency 2023 as many as 31 samples with purposive sampling technique. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using person's R test, data processing using computerized SPSS program IBM version 25.0. The most age is early adulthood and early adulthood, namely 18 people (58.1%), the most anxiety level is moderate anxiety, namely 12 people (38.7%), the most pain degree is moderate pain, namely 13 people (41.9%), and there is a relationship between the anxiety level of elective sectio caesarea patients with the degree of postoperative pain at Sungai Dareh Hospital, Dharmasraya Regency 2023 (p=0.000). There was a significant different of average leukocyte count between appendicitis and appendicitis complication also there was a significant correlation between onset of abdominal pain with severity of pediatric acute appendicitis with strong power correlation. The most age is early adulthood, the highest level of anxiety is moderate anxiety, the highest degree of pain is moderate pain, and there is a relationship between the anxiety level of elective sectio caesarea patients with the degree of postoperative pain at Sungai Dareh Hospital, Dharmasraya Regency 2023.